Transition molecular structures between block copolymers and hyperbranched copolymers suitable for toughening epoxy thermosets. (June 2021) - Sajjad, Muhammad; Zhao, Zhongfu; Zhu, Xiuling; Shi, Yue; Zhang, Chunqing
Abstract: Various toughening agents had been explored to overcome the intrinsic brittleness of epoxy thermosets. While they effectively toughened epoxy thermosets, however, usually produced plasticizing effect, leading to compromised thermal stability, modulus and glass transition temperature ( T g ). Herein dumbbell-shaped SEBS-g-PEG copolymers, owning transitional molecular structures between block copolymers and hyperbranched copolymers, were synthesized via grafting methoxypolyethylene glycol (PEG) onto both end blocks of polystyrene-b-poly(ethylene-ran-butylene)-b-polystyrene (SEBS). They not only had good compatibility with epoxy thermosets without plasticizing effect, but also could form micro-phase separation morphology suitable for toughening epoxy thermosets via combining the advantages of block copolymers and hyperbranched copolymers. At higher branching density, their 10% load could increase ~230% KIC and impact strength without sacrificing thermal stability, T g, flexural strength and modulus. The morphology results showed that their soft nanostructures' size increased and the phase interfaces became blurred as increasing the branching density in SEBS-g-PEG. Thus, the toughening mechanism was attributed to the strengthened bonding between the interphases and the enlarged size of soft nanostructures. Graphical abstract: Image 1 Highlights: A novel copolymer synthesized by grafting polyethylene glycol (PEG) on SEBS to toughen epoxy thermosets. Considerable toughening of epoxy thermosets were reported without sacrificing other mechanical and thermal properties. No plasticizing effect was reported. The toughening mechanism was particularly due to strong bonding between the interphases and soft components ( Wt PEB  +  Wt PEG ).